MARGINALISASI PEREMPUAN DALAM BERITA ONLINE INDONESIA (ANALISIS WACANA KRITIS SARA MILLS) - Neng Windi Agustina Dewi; Agus Hamdani (Indonesian language and literature education program Majapahit Islamic University, 2023)
Discourse analysis is a method used to uncover the meaning and communication messages present in a text, both in its textual and contextual aspects. This means that the meaning of a text or communication message cannot solely be derived from the explicit written text. Sara Mills' discourse model focuses on discourses about feminism, emphasizing the positions of subjects and objects within the text. Feminist discourse highlights how a text represents women. In reality, women are often portrayed as inferior and in the wrong compared to men in texts. The approach used in this analysis is Sara Mills' discourse approach. The author examines a discourse for analysis titled